SOFT TISSUE PERFUSION EVALUATION ALGORITHM IN THE SCHEME OF GUNSHOT DEFECTS “CLOSURE” - Khomenko, I.P.; Lurin, I.A.; Nehoduiko, V.V.; Tertyshnyi, S.V.; Popova, O.M.; Vastyanov, R.S.; Weis, B. (World of Medicine and Biology, 2023)
The purpose of the study was to determine indicators for the soft tissue perfusion evaluation in the scheme of gunshot defects “closure” using a variety of flaps from V–Y and Keystone till “propeller” and free flaps. A thermal imaging camera FLIR C2 with an integrated temperature gauge was used to obtain thermometric images together with a digital photograph of the scanned anatomical area. Microcirculation in damaged tissues plays an important role in wound substrate and the future flap in certain anatomical structure viability ensuring. That’s why its important to determine the features of the soft tissues perfusion fire transformation and the place of the corresponding blood supply from where it is possible to “raise” the flap in the future. The original dynamic multimodal concept using DDT and sonographic evaluation of soft tissue perfusion allows to look at the specific gunshot wound changes in a new way and to plan strategically the optimal path of reconstructive-plastic recovery. The thermographic and sonographic criteria uniqueness for soft tissue perfusion assessing in the context of large gunshot defects closing are reliable and objective, allow to assess the condition of the future wound bed and edges. They can be used not only to evaluate the wound before closing the defect but also to correct further tactics in the large defects or wounds treatment that do not heal for a long time.